2019
DOI: 10.1093/jisesa/iey138
|View full text |Cite
|
Sign up to set email alerts
|

Food Consumption Utilization, and Life History Parameters ofHelicoverpa armigera(Lepidoptera: Noctuidae) Reared on Diets of Varying Protein Level

Abstract: Helicoverpa armigera (Hübner) is an important pest of crops worldwide, and several studies have focused on the development of this species on different artificial diets. However, studies evaluating the insect’s food consumption and utilization using nutritionally different diets are scarce. The aim of this study was to evaluate the biology and to compare the consumption and use of food by H. armigera larvae on diets with different protein levels provided by several dietary ingredients used in the diets. The nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 26 publications
0
7
0
1
Order By: Relevance
“…Likewise, nutritional indices also used to study ingestion, digestion, assimilation, and food conversion of other Lepidopteran larvae, such as Helicoverpa armigera (Naseri et al, 2010;Fite et al, 2018;Truzi et al, 2019). Although the nutritional parameter varied in different species, larval instars, and feeding times, it was crucial to determine the fitness of insects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, nutritional indices also used to study ingestion, digestion, assimilation, and food conversion of other Lepidopteran larvae, such as Helicoverpa armigera (Naseri et al, 2010;Fite et al, 2018;Truzi et al, 2019). Although the nutritional parameter varied in different species, larval instars, and feeding times, it was crucial to determine the fitness of insects.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, numerous researches on biology and nutrition have been carried out. The focus of these studies was based on different varieties of the same crop (Naseri et al, 2010;Rosa-Cancino et al, 2016;Barcelos et al, 2019), genetically-modified plants (Ramalho et al, 2011;Sousa et al, 2016), or artificial diets (Pinto et al, 2019;Truzi et al 2019). Less research compared the life parameters among different hosts.…”
Section: Introductionmentioning
confidence: 99%
“…The most important nutritional factors are the protein and carbohydrate levels, especially their proportions, as these are fundamental components for growth and development, and are part of the composition of enzymes and hormones ( Bae & Sicher 2004 , Sarate et al 2012 ). Studies on lepidopterans such as Plodia interpunctella (Hübner, 1813) (Lepidoptera: Pyralidae) and Helicoverpa armigera (Hübner, 1808) (Lepidoptera: Noctuidae) have shown that low-protein diets promote changes in developmental period, weight and larval mortality, pupation rate, percentage of adult emergence, and nutritional indices ( Borzoui et al 2018 , Truzi et al 2019 ).…”
mentioning
confidence: 99%
“…The methodology recommended by Truzi et al [24], based on Scriber and Slansky [25], was used to estimate the quantitative nutritional parameters of the 4 th instar larvae of A. ipsilon as follows: the weight of feces produced (F), food…”
Section: Anti-nutritional Activities Of the Tested Bos Against A Ipsilon Larvaementioning
confidence: 99%
“…The current results in Table 8 showed that ECI values decreased when the larvae were exposed to the most toxic oils compared to the control at 28 ECD reflects metabolic efficiency and can be reduced by lowered the ECD or enhanced metabolic cost. As a response to decreased assimilation, more food is ingested, which increases RCR [24]. Both M. hortensis and A. santolina increased the food conversion efficiencies ECI and ECD.…”
Section: Toxicity Effects Of the Tested Bos On The Nutritional Indices Of A Ipsilonmentioning
confidence: 99%